A backup protection scheme for the transmission lines based on the directional traveling wave and waveform similarity. (May 2023) - Zhang, Yuhan; Wang, Shunliang; Liu, Tianqi; Li, Xiaopeng; Beng Gooi, Hoay; Ghias, Amer M.Y.M.; Xu, Ruiting; Chang, Tianyu
Highlights: The backup protection scheme based on traveling wave and waveform similarity is proposed for the VSC-HVDC transmission line. The difference in 1-mode forward and backward traveling waves between internal and external faults are proven theoretically. The difference in instantaneous currents between faulty-pole and unfaulty-pole DC lines are proven theoretically. The protection scheme has superiorities in fault resistance tolerance (2, 000 Ω) and quicker fault judgment (less than 4 ms). The protection scheme can identify the double-pole-to-ground fault with unequal positive-pole and negative-pole fault resistances accurately. Abstract: The voltage source converter based high voltage direct current (VSC-HVDC) system is a practical solution to improve renewable energy integration, flexible consumption, and wide-range complementarity. Because the DC line fault must be cleared within a few milliseconds, a reliable and rapid identification of faulty lines and poles is crucial. Unfortunately, the traditional backup protection cannot respond to internal faults fast enough and is sensitive to fault resistance. What is worse is that a double-pole-to-ground fault with unequal positive-pole and negative-pole fault resistances cannot be identified by most of the existing protection methods. The paper proposes a pilot backup protection based on directional traveling wave and waveform similarity for VSC-HVDC transmission lines to compensate for the drawbacks. The fault characteristic of 1-mode directional traveling waves and the waveform similarity of instantaneous currents of DC lines are elaborated theoretically. Based on the analyses, the protection is established, and the four-terminal VSC-HVDC grid is modeled in PSCAD and OPAL-RT. Detailed theoretical analyses and extensive simulation/experiment results have proven that the proposed protection scheme has higher reliability, selectivity, rapidity, and sensitivity. Compared with the existing backup protections, the proposed protection scheme has superiorities in fault resistance and distance tolerance (2, 000 Ω and the entire length of DC lines), fault differentiation of double-pole-to-ground fault with unequal positive-pole and negative-pole fault resistances, immunity from signal noise and measurement error interference, and quicker fault judgment (less than 4 ms). © 2017 Elsevier Inc. All rights reserved.